Sensory Evaluation and Consumer Preference of a Tempeh–Beef Burger Prototype for Urban Markets - Prabowo, Ivy Dian Puspitasari; Mau, Daniel Pandu; Lestariningsih, Titin; Tjahjadi, kezia; Hidayah, Nani Kharisma Nur; Tjahjono, Prijo (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
Urban culinary development creates opportunities to reintroduce local ingredients in formats that meet modern consumer preferences for taste, nutrition, and attractive presentation. This study explored the acceptance of a tempeh-based burger (ITBurger) as an innovative soybean product for urban markets. A total of 20 urban consumers aged 18–30 participated in a controlled sensory evaluation. The burger patty was formulated with 60% steamed tempeh and 40% lean ground beef, then assessed for taste, texture, aroma, and appearance using a 9-point hedonic scale. Participants also identified the primary reason for their preference among taste, texture, appearance, or nutritional value. Results showed high overall acceptance, with taste receiving the highest mean score (8.2 ± 0.5), followed by appearance (8.0 ± 0.4), texture (7.8 ± 0.6), and aroma (7.6 ± 0.7). Taste was the most frequently cited reason for liking the product (50%), while appearance and texture each accounted for 20%, and nutritional value 10%. These findings confirm that flavor and visual appeal are the key drivers of consumer acceptance, while health benefits play a secondary role. The positive response to a tempeh–beef hybrid highlights the potential of flexitarian approaches to reposition traditional soybean products as modern, appealing foods. This model offers a practical pathway for small food enterprises to promote healthy, locally based innovations in urban culinary markets.